PERAN EMPLOYEE ENGAGEMENT TERHADAP EMPLOYEE PERFORMANCE - Rizka Himawaty; Widodo (Universitas Lambung Mangkurat, 2022)
This study aims to measure the role of Employee Engagement as a mediation of the influence of Work Conditions and Professional Identity, so as to increase Employee Performance. The research analysis unit is located in one of the bureaus at the Police Agency in Central Java. The type of research in this study is in the form of Explanatory Research, with the number of samples based on the census method, which means that there are 57 respondents. The analytical tool used in this study is Structural Equation Modeling (SEM) with the SmartPLS (Partial Least Square) Student Version application. The results of this study indicate a significant positive effect between Work Conditions on Employee Engagement, Work Conditions on Employee Performance, Professional Identity on Employee Engagement, Professional Identity on Employee Performance and Employee Engagement on Employee Performance. In addition, Employee Engagement can mediate the influence of Professional Identity on Employee Performance, while Employee Engagement cannot mediate the influence of Professional Identity on Employee Performance.